Root powder extract, phytochemical studies & preparation of herbal formulation tinospora cordifolia asava - M, Samuel; J, N. Suresh Kumar; Sk, Mujubur Rehman; S, Sathvika; V, Anasuya Vibhavari; Y, Vyshnavi; P, Siva Prasad (International Journal of Indigenous Herbs and Drugs, 2024)
Asava, a traditional formulation in Ayurveda, is renowned for its superior preservation and enhanced therapeutic efficacy. This phenomenon is largely attributed to the intricate process of fermentation facilitated by a consortium of microbes. Microbial activity not only extends the shelf-life of Asava but also transforms its constituent ingredients into potent therapeutics through biotransformation. The alcohol-aqueous milieu generated during fermentation not only preserves the formulation but also facilitates improved drug delivery within the body. This milieu, predominantly produced by microbial action, acts as a medium for the potentization of drugs, enhancing their bioavailability and efficacy. Moreover, the biotransformation mediated by native microbes leads to the synthesis of novel compounds with enhanced therapeutic properties, thereby elevating the overall efficacy of Asava. The preservative properties inherent in these formulations, coupled with microbial-mediated potentization, underscore the significance of microbial fermentation in augmenting the therapeutic potential of Asava in Ayurveda.